The Estimation of Soil Trace Elements Distribution and Soil-Plant-Animal Continuum in Relation to Trace Elements Status of Sheep in Huangcheng Area of Qilian Mountain Grassland, China - Hui WANG; Yong-ming LIU; Zhi-ming QI; Sheng-yi WANG; Shi-xiang LIU; Xia LI; Hai-jun WANG; Xiao-li WANG; Xin-chao XIA; Xin-qiang ZHU (Journal of Integrative Agriculture, 2014)
The purpose of the present study was to survey contents of trace elements of Cu, Mn, Fe, and Zn in the surface layer (0-20 cm) in the soil, pasture and serum of sheep in Huangcheng area of Qilian mountain grassland, China. Also the soil-plant-animal continuum was analyzed. Soil (n=300), pasture (n=60), and blood serum samples from sheep (n=480) were collected from Huangcheng area of Qilian mountain grassland, China. The contents of trace element in the samples were analyzed by atomic absorption spectrophotometer after digestion. The soil trace elements density distribution shows a ladder-like pattern distribution. Equations developed in the present study for prediction of Fe (R2=0.943) and Zn (R2=0.882) had significant R2 values.